Pengaruh Pembiayaan Murabahah dan Lama Pengembalian Pembiayaan terhadap Perkembangan UMKM pada PNM Mekaar Syariah - Cut Diah Syavira; Kamilah K; Nurul Inayah (MAMEN: Jurnal Manajemen, 2024)
The aim of this research is to find out whether murabahah financing and the length of murabahah repayment have an effect on the development of UMKM. This research method is quantitative research, the research location studied is PT Permodalan Nasional Madani Mekaar Syariah Percut Sei Tuan Branch. The population in this study were 100 customers of PT Permodalan Nasional Madani Mekaar Syariah Percut Sei Tuan Branch, the samples taken were customers of PT Permodalan Nasional Madani Mekaar Syariah Percut Sei Tuan Branch, the data analysis technique used in this research was multiple linear regression analysis. The results of this research are that murabahah financing has an influence on the development of UMKM, we can see this from the calculated t-value for the financing variable (X1) of 5.813 > t-table value of 1.66071 and the significance is smaller than 0.05 (0.0491 < 0 .05). For the murabahah return time variable, the t-calculated value for the return time variable (X2) is 3.825 > t-table value 1.66071 and the significance is smaller than 0.05 (0.005 < 0.05). Based on the results, the calculated F is 8.370 and the F table is 3.09 while the significance is 0.004. It can be seen that the significance value from the table above is smaller than the value 0.05, which means that murabahah financing and the length of repayment together have an influence on the development of UMKM.